Towards an Improved Software Project Monitoring Task Model of Agile Kanban Method - Hamzah Alaidaros; Mazni Omar; Rohaida Romli (International Journal of Supply Chain Management, 2018)
Agile Kanban method recently is gaining increasing attention and popularity in software development organizations (SDOs). This method has numerous advantages that make it performs better than other Agile methods in terms of managing software projects. However, different studies revealed that this method has significant challenges that negatively impact the scheduling of the development process. Therefore, late delivery of software projects may occur, thus the rate of projects failures will be increased. In response, this paper aims to explicate the current challenges in progress monitoring task of Agile Kanban method. Accordingly, the results gave insights to bridge that gap by developing an improved software project monitoring task model of Agile Kanban method. To do so, we identified the components and criteria that affect software project monitoring task, and then an initial model has proposed. The initial model consists of three main components, which are (1) extending progress tracking, (2) generating optimum WIP limits, and (3) visualizing useful insights for workflow. Further research can be focused on developing and evaluating the proposed model through discussion with the knowledge and domain experts.